History of Rakhine State and the Origin of Rohingya Muslims - Mohajan, Haradhan Kumar (Center for Southeast Asian Social Studies (CESASS), 2019)
Myanmar is a resource-rich country especially in oil and gas. The country is involved in ethnic conflicts since its independence in 1948. Recently violation of human rights against the Rohingya Muslims become severs. The main cause of Rohingya crisis is a question about its origin. Rakhine (or Arakan) is a State located in the west coast of Myanmar. The population of Arakan State is largely agrarian and more than 43.5% live below the poverty line. The Rohingya, a Muslim ethnic minority group in Rakhine, consider as the most persecuted, vulnerable, and oppressed minorities around the globe. Recently, the persecution on Rohingya Muslims has increased due to Buddhist nationalism in Myanmar. Rohingyas are continued to suffer from several forms of restrictions and human rights violations in Myanmar due to deny Myanmar citizenship. They are victim of various oppressions, such as, arbitrary taxation, land confiscation, destruction of mosques, torture and ill-treatment, extrajudicial executions, restrictions on movements, forced eviction and house destruction, forced laborers on roads and at military camps, and financial restrictions on marriage. Oppression on Rohingya started since 1962, when General Ne Win took power of Myanmar after a coup. Since the 1970s, a number of crackdowns on the Rohingya in Rakhine have forced hundreds of thousands to flee to neighboring countries. Sever Rohingya oppression took place in 2017 and 2018. More than one million Rohingya have migrated in Kutupalong-Balukhali, and Nayapara refugee camps, respectively, in Ukhia, and Teknaaf of Cox?s Bazar district of Bangladesh. This article deals with the origin of Rohingyas and their citizenship in the Rakhine State of Myanmar.